Ruthenium Inlaying Porous Aromatic Framework for Hydrogen Generation From Ammonia Borane - Cui, Peng; Ren, Hao; Zhu, Guangshan (Frontiers in Materials, 2019)
Porous organic frameworks (POFs) are a new family of porous materials, which are characterized by high chemical and thermal stabilities, structural design-abilities, chemical functionalities, high porosities, etc. Designable skeletons of POFs lead to different applications in many fields. Herein, we report a porous aromatic framework PAF-72 synthesized via ionothermal reaction. The inherently nitrogen contained skeleton of PAF-72 is beneficial for introducing catalytic active center Ruthenium, which is verified by ICP, TGA, and TEM element mapping. Besides, Ru/PAF-72 shows excellent activity in hydrogen generation from hydrolysis of ammonia borane and good cyclic performance.